2019
DOI: 10.3390/s20010235
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Rescue System with Online Multi-Agent SLAM Framework

Abstract: A novel and an efficient rescue system with a multi-agent simultaneous localization and mapping (SLAM) framework is proposed to reduce the rescue time while rescuing the people trapped inside a burning building. In this study, the truncated signed distance (TSD) based SLAM algorithm is employed to accurately construct a two-dimensional map of the surroundings. For a new and significantly different scenario, information is gathered and the general iterative closest point method (GICP) is directly employed inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Specifically, the mAP of the YOLO v2 model is 99%. Nevertheless, based on the class-wise detection results, as indicated in Table 5 , the proposed models outperformed the existing models 9 , 39 , 40 . Besides, although the dataset used is unbalanced, the overall accuracy in the study shows more than 98% to 100% in identifying between the same species and gender of Aedes aegypti , Aedes albopictus , Culex quinquefasciatus (Suppl.…”
Section: Discussionmentioning
confidence: 91%
“…Specifically, the mAP of the YOLO v2 model is 99%. Nevertheless, based on the class-wise detection results, as indicated in Table 5 , the proposed models outperformed the existing models 9 , 39 , 40 . Besides, although the dataset used is unbalanced, the overall accuracy in the study shows more than 98% to 100% in identifying between the same species and gender of Aedes aegypti , Aedes albopictus , Culex quinquefasciatus (Suppl.…”
Section: Discussionmentioning
confidence: 91%
“…In the overlap-based map merging methods [5], [14], [17], map merging is conducted by finding and matching the overlapping areas using additional features extracted by mathematical transform methods such as Hough transformation [15] and Radon transformation [16]. TSD (truncated signed distances) grid-based map merging algorithm [17] has been developed to perform multi-agent TSD-SLAM. Their algorithm was tested in real rescue systems with smart helmets equipped with IMU (inertial measurement unit) and LIDAR (light detection and ranging) sensors.…”
Section: B Related Workmentioning
confidence: 99%
“…On the one hand, regarding the navigation time in a burning building, researchers in [20] developed a platform to reduce the time with a multi-agent simultaneous localisation and mapping (SLAM) technique. The results indicated that the built map was more accurate than the map obtained using the conventional TSD-SLAM.…”
Section: Location Estimation For Navigation and Firefighter Trackingmentioning
confidence: 99%